Failure to Launch: Cost of Living and Living Standards in Peru during the 19th Century - Arroyo Abad, Leticia (Economia, 2016)
Based on a variety of archival sources, this paper presents estimations for cost of living and living standards for Lima, Peru during the 19th century. During this century Peru experienced deep swings in economic activity marked by the independence wars, the War of the Pacific, and a commodity boom. These new series show that a sizable inflationary period during the guano age had dampening effects on the living standards of the popular class. While living standards peaked by mid 1850s, GDP per capita did not do so until two decades later. These results suggest that the guano bonanza failed to lift working-class living standards above subsistence levels. Even though living standards climbed steadily, almost reaching those of England, all these gains were lost by the end of the century.